Generation Y’s sustainability attitude-behaviour gap - Bernardes, João Pedro (2019)
This paper intends to study the gap between the attitude Millennial consumers (or Generation Y) have towards sustainability and sustainable purchasing habits and what they actually do in terms of their green purchasing behaviour. In order to understand this gap, some internal and external influencing factors were obtained from the literature review which can positively or negatively influence the green purchasing behaviour of the Millennial consumers. They are: Awareness, Financial availability, Personal benefits, Subjective norm and Trust, and were ana-lyzed in the form of a questionnaire that was applied to Millennials across Portugal. To further this research, some of the influencing factors were selected in order to obtain a better under-standing of the attitude-behaviour gap regarding the purchase of sustainable footwear. With this paper it is possible to conclude that although Gen Y’s attitude towards sustainability is very positive, they still don’t have a green purchasing behaviour.